2009
DOI: 10.1177/0363546509351143
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Selection in Articular Cartilage Lesions of the Knee

Abstract: Lesion size, activity level, and patient age are factors that should be considered in selecting treatment of articular cartilage lesions of the knee. In addition, these factors are a step toward evidence-based, instead of surgeon-preferred, treatment of articular cartilage lesions of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
154
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(166 citation statements)
references
References 39 publications
2
154
1
6
Order By: Relevance
“…In the case of orthobiologic treatment of knee disorders it is important to realise that cartilage repair does nothing else than treating the surface. In some cases cartilage repair alone is able to solve a problem, but only if nothing else than the cartilage lesion was causing the symptoms of the patient [2]. In most cases a cartilage lesion is just the tip of an iceberg.…”
mentioning
confidence: 99%
“…In the case of orthobiologic treatment of knee disorders it is important to realise that cartilage repair does nothing else than treating the surface. In some cases cartilage repair alone is able to solve a problem, but only if nothing else than the cartilage lesion was causing the symptoms of the patient [2]. In most cases a cartilage lesion is just the tip of an iceberg.…”
mentioning
confidence: 99%
“…Over 5 years follow-up, no matter which surgical technique has been used, the clinical result is the same and no significant difference remains in the outcomes that is dependent to the size of the defect. In four randomized studies, it has been shown that age is also a parameter that most influenced the cartilage repair, as young patients under the age of 30 years appear to have a better healing independently of the surgery technique compared with patients over the age of 30 years [31].…”
Section: Current Cartilage Repair Techniquesmentioning
confidence: 99%
“…For this reason and due to its minimally invasive nature, technical ease, limited surgical morbidity, low costs and because it does not prevent the application of other cartilage repair procedures that may be needed in the future, microfracture has gained popularity over the past two decades [8][9][10]. It is now a common first-line treatment for patients with cartilage defects of the knee [11,12].…”
Section: As Well As Tomentioning
confidence: 99%